Nutrients loads at Shatt Al-Arab river in Basrah city, Iraq - Alhello, Abdulzahra A.; Talal , Ammar A.; Abdulrasool, Raghad M. (Iraqi Journal of Aquaculture, 2023)
The study included the nitrates, phosphates loads and some properties of water quality in the Shatt Al-Arab River at Basra city center . There were used to identifying the state of water and nutrient movement in this part of the River starting from the Shilha location north of Al-Hartha to ​​Al-Bahadriyah north of Abu Al-Khasib, which represents the section that contains dense human population at Basra city center. Fourteen sampling stations were selected within the study area during the summer and winter periods, as well as during the morning and evening at the same day. The study showed that the phosphate and nitrate salts have not transfer out of this river section. Also there were no significant impact of the side river branches on the water quality of the Shatt al-Arab River because of the low discharges from these branches compared to discharge of the main Shatt al-Arab River.